Lyrical And Musical Genres in Goran's Poems - Abdulla, Kanyaw Bakr; Hama Faraj, Dilan Salam; Ali, Srwa Tahir; Ali, Aram Omer; Mahmood, Aram Omer; Karim, Alim Abdulla; Abdulla, Mawdud Jabar (Journal of Linguistics and Social Sciences, 2024)
This research is entitled: (Lyric and melody, Genres in Goran's Poems) which is a new look at two aspects, namely (genre, external and internal music of Goran's poems). It attempts to present the genre in all its details and characteristics, on the other hand, to determine it according to the characteristics of the lyrical genres of Goran's poems. Because lyrical genres are related to many aspects such as hymns, songs, poems, etc. Therefore, an attempt has been made to explain the aspects that are directly related to lyricism and create mutual influences and reactions. Therefore, "Outer and Inner Music in Goran's Poems" will be part of this research. The research was conducted according to the method (descriptive_analytical), which explains the lyricism of Goran in terms of genres and at the same time interprets the outer and inner melody of the poet's poems. This paper consists of an introduction, two parts, conclusions and a list of sources.